The Impact of Accelerated HF-rTMS on Canine Brain Metabolism: An [18F]-FDG PET Study in Healthy Beagles - Xu, Yangfeng; Peremans, Kathelijne; Courtyn, Jan; Audenaert, Kurt; Dobbeleir, Andre; D'Asseler, Yves; Achten, Eric; Saunders, Jimmy; Baeken, Chris (Frontiers in Veterinary Science, 2022)
Background: Repetitive transcranial magnetic stimulation (rTMS) has been proven to be a useful tool for the treatment of several severe neuropsychiatric disorders. Accelerated (a)rTMS protocols may have the potential to result in faster clinical improvements, but the effects of such accelerated paradigms on brain function remain to be elucidated. Objectives: This sham-controlled arTMS study aimed to evaluate the immediate and delayed effects of accelerated high frequency rTMS (aHF-rTMS) on glucose metabolism in healthy beagle dogs when applied over the left frontal cortex. Methods: 24 dogs were randomly divided into four unequal groups: five active (n=8)/ sham (n=4) stimulation sessions (five sessions in one day), 20 active (n=8)/ sham (n=4) stimulation sessions (five sessions/ day for four days), respectively. [18F] FDG PET scans were obtained at baseline, 24 hours poststimulation, after one and three months post the last stimulation session. We explicitly focused on four predefined regions of interest (left/right prefrontal cortex and left/right hippocampus). Results: One day of active aHF-rTMS - and not sham - significantly increased glucose metabolism 24h post-active stimulation in the left frontal cortex only. Four days of active aHF-rTMS only resulted in a nearly significant metabolic decrease in the left hippocampus after 1 month. Conclusions: Like in human psychiatric disorders, active aHF-rTMS in healthy beagles modifies glucose metabolism, although differently immediately or after one month post stimulation. aHF-rTMS may be also a valid option to treat mentally disordered dogs.